2012
DOI: 10.1136/sextrans-2012-050535
|View full text |Cite
|
Sign up to set email alerts
|

Screening tests forChlamydia trachomatisorNeisseria gonorrhoeaeusing the cobas 4800 PCR system do not require a second test to confirm: an audit of patients issued with equivocal results at a sexual health clinic in the Northwest of England, UK

Abstract: Equivocal reports introduce delays to patient management, while the risk of unnecessary antibiotic therapy appears acceptable to most patients. The cobas 4800 CT/NG PCR screening assay can achieve UK testing standards (PPV >90%) for chlamydia, and low prevalence gonorrhoea in urine without supplementary tests. A patient-led confirmation algorithm is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…However, it should be noted that a limitation and potential bias of this study was that the PCR and culture were, for the most part, not performed on the same sample type (i.e., PCR was performed on urine samples and bacterial culture on genital swabs). Nevertheless, our findings are supported by two recent studies which showed that the cobas N. gonorrhoeae test had lower levels of false positivity than predecessor assays (9) and does not require a confirmation test for N. gonorrhoeae in urine specimens (10). Despite recent calls to move to NAAT routinely for pharyngeal and rectal testing, it is still recommended that positive results from these sites be confirmed by supplemental assays (5).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, it should be noted that a limitation and potential bias of this study was that the PCR and culture were, for the most part, not performed on the same sample type (i.e., PCR was performed on urine samples and bacterial culture on genital swabs). Nevertheless, our findings are supported by two recent studies which showed that the cobas N. gonorrhoeae test had lower levels of false positivity than predecessor assays (9) and does not require a confirmation test for N. gonorrhoeae in urine specimens (10). Despite recent calls to move to NAAT routinely for pharyngeal and rectal testing, it is still recommended that positive results from these sites be confirmed by supplemental assays (5).…”
Section: Discussionsupporting
confidence: 74%
“…gonorrhoeae NAAT assays, our data show that a urine specimen alone is not sufficiently sensitive (86.7%) to screen for N. gonorrhoeae in females (19,20). We have previously shown that interference from mucopurulent discharge in N. gonorrhoeae-positive patients causes failed cobas 4800 results (12), and this has also been reported by Hopkins et al (10). Most failed results can be resolved by treatment with Sputasol (1.4% DTT; Oxoid) (12).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Samples were tested for Chlamydia with the Roche Cobas 4800 CT/NG PCR assay. 12 Data were analysed in Microsoft Excel. A two-tailed test of proportions was used to determine confidence intervals and P values.…”
Section: Methodsmentioning
confidence: 99%
“…The Roche cobas 4800 CT/NG assay is a later-generation NAAT method, and the NG component of the assay utilizes a dual-target approach, using two assays to detect sequences within the directrepeat (DR-9) region (3). Performance data to date show excellent sensitivity and specificity for urogenital specimens (3-7), and it has been suggested that the assay does not require a second test to confirm urogenital positive results (6). Also, to our knowledge, there have been no definitive reports of the assay cross-reacting with commensal Neisseria strains (3,8); while initial testing in a study by Tabrizi et al (8) showed that the cobas 4800 NG assay cross-reacted with two commensal Neisseria strains, both were negative upon retesting using fresh cultures (8).…”
mentioning
confidence: 99%